Color in food : technological and psychophysical aspects - Buera, Maria del Pilar; Caivano, Jose Luis (CRC Press, 2012)
"Focusing on food technology and psychophysical aspects of food color and appearance, this book covers color research and its application in various stages of food production, processing, commercialization and consumption. It comprises selected best keynote lectures and papers presented from the Meeting of the International Color Association held at Mar del Plata, Argentina, in October 2010. The text is organized into five sections that describe food color and appearance, food colorimetry and color scales, color change as a quality index of food, color as an index of food composition and properties, color in packaging, sensory evaluation and preferences, and the food environment"-- Provided by publisher